An Intellectual Decision System for Classification of Mental Health Illness on Social Media using Computational Intelligence Approach - Sujithra, M.; Rathika, J.; Velvadivu, P.; Marimuthu, M.; Abhinaya.V; R, Reshma. (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Despite the advantages, the significant increase in the use of social media has also reflected in causing various health consequences. Social media provides a platform for people to directly express their emotions about the products they buy and also make suggestions. As a result of this, the social media users are facing more decision-making challenges. The emotions obtained from social media are based on polarity ranking, but this measurement of emotions is insufficient in real-time. A novel model should be designed in such a way that it correctly categorizes the human emotions via social media. This research work has attempted to predict the human emotions based on their social media posts, comments, and so on. Here, the machine learning algorithms are used to intelligently classify the human emotions and provide a better decision-making model.